Inclined and multi-directional surface impacts accelerate biodegradation and improve mechanical properties of pure iron. (July 2021) - Bagherifard, Sara; Naderi Beni, Rasool; Kajanek, Daniel; Donnini, Riccardo; Monti, Stefano; Molla, Mauro Filippo; Hadzima, Branislav; Guagliano, Mario
Abstract: Impact based surface treatments with adequate kinetic energy have favorable effects on promoting cell-substrate interactions, reducing bacterial adhesion, and enhancing fatigue performance of metallic biomaterials. Here, we used both numerical and experimental approaches to evaluate the potential of these treatments for addressing the major issue associated with the application of pure iron in biomedical implants, i.e. its low corrosion rate. Despite the efficiency of impact based surface treatments in modulating the degradation rate of pure iron, the maximum reported depth of the affected surface layer is still limited, even when extreme process parameters are used. To address this issue, herein, two impact based treatments were adjusted to trigger the dislocation activities that facilitate grain refinement in pure iron using multi-directional inclined impacts. An alternative approach of severe shot peening (SSP) was developed and compared with ultrasonic shot peening (USP). The effect of both treatments and variations of their key parameters were analyzed considering the significant role of shear bands and dislocation cells in the grain refinement mechanism of pure α-iron. Microstructural, mechanical and electrochemical properties of the treated material were analyzed. The observations showed extension of the grain refined layers for the specimens subjected to multidirectional oblique impacts compared to the ones treated in the classic manner using normal impacts. The results imply that by adapting peening parameters, it would be possible to effectively create a thick surface layer with properties that can accelerate the biodegradation of pure iron boosting its potential to meet clinical requirements for temporary hard tissue implants.